The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0238160
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of hematological and immunological markers in COVID-19 infection: A meta-analysis of 6320 patients

Abstract: Objective Evidence-based characterization of the diagnostic and prognostic value of the hematological and immunological markers related to the epidemic of Coronavirus Disease 2019 (COVID-19) is critical to understand the clinical course of the infection and to assess in development and validation of biomarkers. Methods Based on systematic search in Web of Science, PubMed, Scopus, and Science Direct up to April 22, 2020, a total of 52 eligible articles with 6,320 laboratory-confirmed COVID-19 cohorts were inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
164
5
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(201 citation statements)
references
References 62 publications
19
164
5
13
Order By: Relevance
“…Among laboratory tests, elevated neutrophil-to-lymphocyte ratio, but not elevated levels of lactate dehydrogenase, C-reactive protein, or D-dimer, were associated with increased mortality. In contrast, decreased absolute lymphocyte counts were associated with increased mortality ( Supplemental Figure 1 and Supplemental Table 2 ), consistent with previous reports ( 22 , 23 ). Administration of anticoagulation was associated with reduced mortality ( Supplemental Figure 1 and Supplemental Table 2 ).…”
Section: Resultssupporting
confidence: 91%
“…Among laboratory tests, elevated neutrophil-to-lymphocyte ratio, but not elevated levels of lactate dehydrogenase, C-reactive protein, or D-dimer, were associated with increased mortality. In contrast, decreased absolute lymphocyte counts were associated with increased mortality ( Supplemental Figure 1 and Supplemental Table 2 ), consistent with previous reports ( 22 , 23 ). Administration of anticoagulation was associated with reduced mortality ( Supplemental Figure 1 and Supplemental Table 2 ).…”
Section: Resultssupporting
confidence: 91%
“… 22 The influence of WBC and CRP has been explored in other publications showing that increases in WBC counts are found in patients with COVID-19 admitted to the ICU while CRP has been observed as a predictor of respiratory failure and thrombotic complications. 23-25 In our series, we found that WBC and CRP were found in patients admitted to the ICU and those with poor outcome. Underlying comorbidities and hospital immobilization, which are known risk factors for venous thrombosis, 26 were present in most of our patients, suggesting that the risk of thrombosis in patients with COVID-19 is likely multifactorial.…”
Section: Discussionmentioning
confidence: 53%
“…These findings in patients with a known history of gynecologic cancer are consistent with prior studies of inflammatory, hematologic, and coagulation markers in COVID-19 infection. Two independent meta-analyses of inflammatory markers in COVID-19 infection among the general population have reported significantly higher inflammatory markers in patients with severe COVID-19 and COVID-19 mortality, including CRP, ESR, ferritin, procalcitonin, and IL-6 [9,21,22]. One meta-analysis also found significant associations between hematologic markers and COVID-19 severity and death, including WBC and D-dimer.…”
Section: Discussionmentioning
confidence: 98%